Effects of Dietary Restriction on PGC-1α Regulation in the Development of Age-associated Diseases - Widjaja, Shefilyn; Antarianto, Radiana D.; Hardiany, Novi Silvia (Current Aging Science, 2024)
Ageing is the most significant risk factor for a number of non-communicable diseases, manifesting as cognitive, metabolic, and cardiovascular diseases. Although multifactorial, mitochondrial dysfunction and oxidative stress have been proposed to be the driving forces of ageing. Peroxisome proliferator-activated receptor γ coactivator α (PGC-1α) is a transcriptional coactivator central to various metabolic functions, of which mitochondrial biogenesis is the most prominent function. Inducible by various stimuli, including nutrient limitations, PGC-1α is a molecule of interest in the maintenance of mitochondrial function and, therefore, the prevention of degenerative diseases. This review involves a literature search for articles retrieved from PubMed using PGC-1α, ageing, and dietary restriction as keywords. Dietary restriction has been shown to promote tissue-specific PGC-1α expression. Both dietary restriction and PGC-1α upregulation have been shown to prolong the lifespans of both lower and higher-level organisms; the incidence of non-communicable diseases also decreased in fasting mammals. In conclusion, dietary interventions may delay ageing by regulating healthy mitochondria in various organs, presenting the possibility of a new primary prevention for many age-related diseases.
Keywords: ageing